2019
DOI: 10.1038/s41598-019-46611-z
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Sweat-Lactate Biosensor Emplsoying a Hydrogel-Based Touch Pad

Abstract: This study is the first report demonstrating proof-of-concept for a hydrogel-based touch sensor pad used for the non-invasive extraction and detection of sweat components. The sensor device was composed of an electrochemical L-lactate biosensor covered with an agarose gel in a phosphate buffer saline. When human skin contacts the agarose gel, L-lactate in sweat was continuously extracted into the gel, followed by in-situ potentiometric detection without controlled conditions. This novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 30 publications
2
78
0
1
Order By: Relevance
“…22−24 Both interface types, however, are commonly used only as reservoirs for subsequent analysis in a decoupled manner with bulky laboratory instruments (e.g., mass spectrometers). Recently, a proof-of-concept of lactate measurement with a sensor-coupled hydrogel was demonstrated for fingertip sweat sampling; 25 however, the key hydrogel sensor performance metrics (including the sensor's limit of detection (LoD), detection range, and selectivity) has not been fully characterized, and its deployment in diverse application spaces has not been demonstrated.…”
mentioning
confidence: 99%
“…22−24 Both interface types, however, are commonly used only as reservoirs for subsequent analysis in a decoupled manner with bulky laboratory instruments (e.g., mass spectrometers). Recently, a proof-of-concept of lactate measurement with a sensor-coupled hydrogel was demonstrated for fingertip sweat sampling; 25 however, the key hydrogel sensor performance metrics (including the sensor's limit of detection (LoD), detection range, and selectivity) has not been fully characterized, and its deployment in diverse application spaces has not been demonstrated.…”
mentioning
confidence: 99%
“…These sensors have shown that they could detect analytes in the concentration range found in human sweat components. Our research group also has focused on developing extended-gate organic transistor-based biosensors for sweat analysis utilizing different types of bioreceptors: antibody, [53][54][55][56][57] enzyme, [58][59][60][61][62][63][64][65][66] and ionophore, 67,68 because, as described below, the organic transistor can be mass-fabricated at low cost using advanced printed technology. The following typical fabrication process was used for our extended gate-type, organic, transistor-based biosensor.…”
Section: Transistor-based Biosensors For Highly Sensitive Sweat Analysismentioning
confidence: 99%
“…Based on these factors, we invented a new sweat extraction and detection device. 66 The sensor was composed of an enzymebased L-lactate sensor and Ag/AgCl reference electrodes, prepared in the same way as described in Fig. 3(a), and were fully covered with an agarose hydrogel including a sweatextraction solution of PBS ( Fig.…”
Section: Sweat Biomarkers and Their Collection/ Detection Techniquesmentioning
confidence: 99%
“…The redox reaction can be also used in potentiometric sensors, [17,18] in which the electron transfer generates open-circuit potential between the reference and enzyme-functionalized electrode. Others include colorimetric sensing that utilizes electrochemical colorimetric indicators, [19] and transistor-based sensing that includes enzyme-functionalized electrodes in transistor configuration.…”
Section: Doi: 101002/mabi202000144mentioning
confidence: 99%